Legal Costs as Damages in the Application of UN Sales Law - Peter Schlechtriem, Freiburg (Journal of Law and Commerce, 2008)
In the literature on the uniform UN sales law (CISG), the decisions in the first and second instances of the Zapata1 case triggered an extraordinarily lively discussion. Simply stated, the case concerned the delivery of painted cookie tins used for packaging Christmas cookies, for which the American buyer (i.e., place of business in the USA), citing flimsy pretexts, refused to pay. The Mexican seller (i.e., place of business in Mexico), sued and was awarded compensatory damages; as part of the damages, the trial court also awarded the plaintiff its attorneys’ fees. At the appellate level, where only the issue of attorneys’ fees was disputed, the appellate court rejected the claim for reimbursement of attorneys’ fees and reversed the trial court decision. [The seller’s] appeal to the U.S. Supreme Court by writ of certiorari was denied. The cases concerned the so-called “American rule,” according to which the parties each bear their own litigation expenses, and in particular their own attorneys’ fees, independent of the outcome of the case. This deviates from German legal understanding and has significant practical consequences. In particular, high attorneys’ fees could lead to the result that the compensatory damages awarded to the plaintiff in actuality fall far short of covering his losses, and for the victorious defendant winning a case can be a pyrrhic victory. Yet, the American rule is not without exceptions, and especially for abusive lawsuits brought on obviously groundless claims, American procedural law permits the losing party bringing such claims to be partially burdened with the cost.Also in cases of especially serious breach of contract, an award of punitive damages could make it possible for the victorious plaintiff to recover his litigation expenses and attorneys’ fees. Nevertheless, in the large majority of cases the American rule leads to the described results, which for German jurists appear at first glance surprising and unacceptable. Especially for foreign parties to a contract who come before an American court and win, the American rule can lead to unpleasant surprises.